Democratization, Litigations and Criminalization of Elections in Nigeria - Bribena, Kelvin (International Journal of Criminology and Sociology, 2022)
The study examines criminalization of elections in Nigeria with the prism lens focused respectively on the 2019 gubernatorial elections in Nigeria. The intention is to further advance the ongoing discourse on how criminality in elections has eroded core democratic values in the country. The source(s) of the data for this discourse are mostly derived from critical stakeholders including the Independent National Electoral Commission (INEC), political parties, aspirants or candidates, voters, election monitors and observers, and various scholarly contributions obtained from the internet. The research concluded with ways to address election criminality in Nigeria.